Mg, O, Br three-element co-doped Li-Y-Cl-S series amorphous solid electrolyte material and preparation method and application thereof
The Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br solves the problems of insufficient room temperature ionic conductivity, interfacial impedance, and air humidity resistance of existing Li-Y-Cl-S amorphous solid electrolytes, thus meeting the requirements of high power density batteries and possessing excellent battery cycle performance and low cost characteristics.
Patent Information
- Application Number
- CN202610827555.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-08-25
AI Technical Summary
Existing Li-Y-Cl-S amorphous solid electrolytes have shortcomings in terms of room temperature ionic conductivity, interfacial impedance, and resistance to air humidity, making it difficult to meet the requirements of high power density batteries.
A Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br was designed using the general chemical formula LiaYbSd-zOzClc-yBryMgw. Combined with high-energy ball milling and low-temperature rapid thermal treatment processes, a stable amorphous structure was formed, which increased the carrier concentration and optimized the interfacial compatibility and environmental stability.
It achieves an increase of approximately one order of magnitude in room temperature ionic conductivity, a reduction in interfacial impedance, a significant improvement in moisture resistance, excellent battery cycle performance, and is suitable for mass production at a low cost.
Abstract
Description
Technical Field
[0001] This invention relates to the field of all-solid-state lithium battery technology, and in particular to a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br, its preparation method, and its application. Background Technology
[0002] All-solid-state lithium-ion batteries, due to their use of non-flammable solid electrolytes, possess higher safety and greater energy density potential, and are considered an important direction for the development of next-generation lithium batteries. Currently, common solid electrolytes mainly fall into two categories: oxide systems and sulfide systems. Oxide solid electrolytes have high chemical stability, but low room-temperature ionic conductivity and high contact resistance at the electrode interface; sulfide solid electrolytes (such as Li7P3S...) 11 (e.g., Li6PS5Cl) can achieve an ionic conductivity of up to 10 at room temperature. -2 It has a flow rate in the range of S / cm and good contact with the electrode interface, but poor chemical stability. When exposed to air, it is prone to violent reaction with moisture to generate toxic H2S gas, which greatly limits its actual manufacturing and use.
[0003] Solid-state halide electrolytes (such as Li3YCl6 and Li2ZrCl6) possess a wide electrochemical stability window and are highly inert to air, with relatively inexpensive and readily available raw materials. Li2ZrCl6, in particular, does not contain expensive or scarce elements, giving it a significant cost advantage. However, the room-temperature ionic conductivity of pure inorganic halides is generally only 10⁻⁶. -4 -10 -3 The S / cm ratio is insufficient to meet the demands of high-power-density batteries. Furthermore, the high interfacial impedance when halides directly contact metallic lithium can lead to reduction decomposition (such as the formation of LiCl), resulting in rapid interfacial degradation and the induction of lithium dendrites. Therefore, improving the ionic conductivity of halide electrolytes and reducing the impedance at the electrode interface while maintaining environmental stability is one of the key issues that urgently need to be addressed in current solid-state electrolyte research.
[0004] To combine the advantages of sulfide and halide materials, researchers have begun to explore their integration, developing halide-sulfide hybrid solid electrolyte systems. For example, Chinese patent CN115676883A discloses a Li-Zr-Cl-S system that, by optimizing the ratio of Li, Zr, Cl, and S, increases the room-temperature ionic conductivity to 10. -3 -10 -2 S / cm, reaching a maximum of 4.34×10 -2 S / cm. Another Chinese patent, CN115966756A, discloses a Li-Y-Cl-S system, which, by adjusting the specific ratio of Li, Y, Cl, and S, achieves an ionic conductivity exceeding 4 × 10⁻⁶ S / cm at room temperature. -3S / cm. These halide-sulfide solid electrolytes utilize the high mobility of sulfide anions and the interfacial stability of chloride anions, achieving a balance between conductivity and stability to some extent. However, these materials still primarily rely on Cl... - Li is a halogen component. + The ion migration kinetics of the Li-Y-Cl-S material exhibit strong lattice confinement, leaving room for improvement. Simultaneously, the material's compatibility with high-energy-density electrodes (such as NMC811 cathodes and lithium metal anodes) remains insufficient. Poor interfacial contact or side reactions lead to increased impedance, affecting the battery's rate performance and cycle life. Although the aforementioned Li-Y-Cl-S material does not contain easily hydrolyzed P2S5 and exhibits improved stability compared to pure sulfides, it still undergoes side reactions with trace amounts of water in air (e.g., Li2S + H2O → H2S), remaining sensitive to environmental humidity. Therefore, it requires preparation and use under dry conditions with a low dew point. Existing pure Li-Y-Cl-S electrolytes show a weight gain of approximately 0.8% and detectable H2S gas concentrations of approximately 0.8 ppm after 72 hours of exposure to dry air; however, after 24 hours of exposure to air with 50% relative humidity, the weight gain exceeds 3-5%, the H2S concentration reaches tens of ppm, and visible material decomposition occurs. Therefore, improving the room-temperature ionic conductivity of Li-Y-Cl-S electrolyte and enhancing its interfacial stability and moisture resistance is essential for achieving high-performance all-solid-state batteries.
[0005] Doping modification has proven to be an effective way to improve the performance of solid-state electrolytes. By introducing impurity elements with different valences or ionic radii into the crystal lattice, the static equilibrium of the original lattice can be broken, creating more lithium-ion migration channels, increasing carrier concentration, and improving interfacial compatibility. For example, doping a small amount of Mg into lithium sulfide Li₂S... 2+ Li can be replaced + Simultaneously forming equimolar amounts of Li + Empty space, thus significantly improving Li + It increases electrical conductivity and lowers the migration energy barrier. Similarly, in oxide and phosphate electrolytes, Mg doping has been widely verified to effectively improve ion migration rates through vacancy mechanisms. Another example is the doping of Y into the halide Li₂ZrCl₆. 3+ Or Ta 5+ High-valence cations can alter the crystal structure and increase the lithium content in the lattice, thereby increasing the room-temperature ionic conductivity from 10... -4 The S / cm order has been increased to the 10 level. -3 S / cm or higher. Regarding interface stability issues, incorporating elements that can form a stable interface layer also has a significant effect: introducing a small amount of oxygen into halides can enhance the structural rigidity of the material and passivate its reactivity with water, thereby significantly improving its moisture resistance. Since oxygen and sulfur both have a molecular weight of 2... - Price, appropriate amount 2-The incorporation of oxygen does not disrupt the charge balance of the material and can improve its chemical stability without significantly reducing ionic conductivity. Experiments have reported the formation of Li6 by incorporating oxygen into the sulfide electrolyte Li6PS5Cl. 05 P0. 99 S4.9O0.1Cl1. 05 At that time, the room temperature ionic conductivity decreased from 10 when oxygen was not doped. -3 The S / cm ratio jumped to 7.49 × 10⁻⁶. -3 The S / cm ratio was improved, and a stable Li3OCl-rich passivation film was generated in situ at the electrolyte / lithium interface, increasing the cycle life of the lithium symmetric battery to 13,000 hours and the critical current density to 1.3 mA / cm². 2 Furthermore, the Cl in the halogen component - Partial replacement with Br, which has a larger ionic radius - This is also an effective strategy to improve lithium-ion mobility: Br - Doping increases the lattice constant, widening the lithium-ion diffusion channels and reducing migration resistance; the coexistence of different halogens can also increase the disorder of anion sites, further improving ionic conductivity. For example, in sulfides like Li7PS... 6- Cl Introducing Br - It is reported that the room temperature ionic conductivity can be increased from 10 -3 S / cm increased to nearly 10 -2 S / cm.
[0006] In summary, existing Li-Y-Cl-S amorphous solid electrolytes still have shortcomings in terms of room temperature ionic conductivity, interfacial impedance, and resistance to air humidity, and need further optimization and improvement. Summary of the Invention
[0007] This invention aims to provide a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br, along with its preparation method and applications. Combining the advantages of individual element doping, this invention achieves a synergistic improvement in ionic conductivity, interfacial stability, and environmental stability while maintaining the stability of the material's amorphous structure. The details of this invention are as follows: The first objective of this invention is to provide a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br, the key technical point of which is that its chemical formula is: Li a Y b S d-z O z Cl c-y Br y Mg w, where 0.1 ≤ z ≤ 0.3, 0 < y ≤ 0.4, 0 < w ≤ 0.3, the value range of a is 5 - 10, the value range of b is 0.5 - 2, the value range of c is 0.4 - 1, and the value range of d is 4 - 5.
[0008] The second object of the present invention is to provide a preparation method of an Mg, O, Br triple - doped Li - Y - Cl - S - based amorphous solid electrolyte material. The technical points are as follows: Step 1: Mix lithium source, yttrium source, sulfur source, chlorine source, bromine source, oxygen source and magnesium source according to the stoichiometric ratio, and perform high - energy ball - milling treatment on the above mixture in an inert atmosphere for 1 - 60 hours to fully mix and react the components to form a uniform precursor powder; Step 2: Rapidly heat the precursor powder to 300 - 600 °C in an inert atmosphere and hold for 0.5 - 2 hours, and then rapidly cool to room temperature to obtain the Mg, O, Br - co - doped Li - Y - Cl - S solid electrolyte powder.
[0009] The third object of the present invention is to provide an application of an Mg, O, Br triple - doped Li - Y - Cl - S - based amorphous solid electrolyte material in a all - solid - state lithium battery. The technical points are as follows: The all - solid - state lithium battery includes a positive electrode, a negative electrode and a solid electrolyte layer disposed between the positive and negative electrodes; the solid electrolyte layer uses the Mg, O, Br - co - doped Li - Y - Cl - S solid electrolyte material according to any one of claims 1 - 4.
[0010] Compared with the prior art, the present invention can achieve the following beneficial effects: 1. High ionic conductivity: The room - temperature ionic conductivity of the material of the present invention is ≥1.2x10 -2 S / cm, which is about one order of magnitude higher than that of the undoped Li - Y - Cl - S material, and the ionic migration activation energy is reduced to less than 0.25 eV, meeting the use requirements of high - power - density batteries.
[0011] 2. Excellent moisture - resistant stability: When exposed to air at 25 °C and 50% relative humidity for 24 h, the mass increase rate of the material is ≤1%, and the H2S release concentration is lower than 5 ppm, which is far better than the undoped material, reducing the dependence on a dry environment during the preparation and use process.
[0012] 3. Good interfacial compatibility: When contacting with a lithium metal negative electrode, a stable passivation layer rich in Li3OCl can be in - situ formed to inhibit the growth of lithium dendrites and interfacial side reactions; it has good compatibility with the NMC811 positive electrode, with low interfacial impedance and long - term stability.
[0013] 4. Good battery cycling performance: The all-solid-state lithium battery using the electrolyte of the present invention has a capacity retention rate ≥ 80% after 400 cycles at 25°C and 0.1C rate, and a capacity retention rate ≥ 75% after 500 cycles, which is significantly better than the battery assembled with undoped materials.
[0014] 5. Simple preparation process: The present invention adopts a high-energy ball milling combined with a low-temperature rapid heat treatment process, without high-temperature long-time sintering, with low energy consumption and controllable process, suitable for large-scale production, and the raw materials are all common industrial chemical raw materials, with low cost. Detailed implementation manners
[0015] A Li-Y-Cl-S-based amorphous solid electrolyte material co-doped with Mg, O, and Br elements, characterized in that the chemical general formula is: Li a Y b S d-z O z Cl c-y Br y Mg w , in the Li-Y-Cl-S system: O is doped in the form of O 2- and partially replaces the sulfur ion S 2- ; Br is doped in the form of Br - and partially replaces the chloride ion Cl - ; Mg is doped in the form of Mg 2+ and partially replaces the lithium ion Li + and is accompanied by the introduction of equimolar Li + vacancies to maintain charge neutrality; where 0.1 ≤ z ≤ 0.3, 0 < y ≤ 0.4, 0 < w ≤ 0.3. Ternary doping within this ratio range can ensure that the material forms a stable single-phase amorphous structure without the precipitation of a second phase. When exceeding the above range, the material properties may deteriorate instead: for example, when the oxygen doping amount is too high (z > 0.3), the lattice may shrink significantly and the ionic conductivity may decrease; when the Br doping amount is too large (y > 0.4), local structural distortion or phase separation may occur, which is not conducive to the stability of the material; when the Mg doping amount is too high (> 0.3), a Mg-containing secondary phase is likely to precipitate, and when it is too low (< 0.05), it is difficult to generate sufficient vacancy effects; the value range of a is 5 - 10, the value range of b is 0.5 - 2, the value range of c is 0.4 - 1, and the value range of d is 4 - 5. As a preferred chemical general formula: Li8YS 5-z O z Cl 1-y Br y Mg w, where 0.1 ≤ z ≤ 0.3, 0 < y ≤ 0.4, 0.05 < w ≤ 0.3. As a preferred amorphous solid electrolyte material, the Mg content is 0.1 at%, O is about 0.2 (20% replaces S), and Br is about 0.2 (20% replaces Cl). Based on this combination, the material chemical formula can be approximately expressed as: Li 8-o.o1 Mg o.o1 YS 4.9 O 0.1 Cl 0.8 Br 0.2 (where Mg o.o1 represents about 0.1 at% of Mg, and its introduction is accompanied by the generation of about 0.01 moles of Li + vacancies to maintain charge balance). It should be understood that the above chemical formula is only an illustrative example, and the content of Li + vacancies in the actual material is equal to the Mg 2+ doping concentration, that is, for every 1 Mg 2+ substituting for Li + , 1 Li + vacancy is formed in the lattice at the same time. Through the above ternary co-doping, the structural characteristics of coexistence of cation vacancies and multiple anion disorders are introduced into the material lattice, making the material tend to form a single-phase amorphous state (glass state). As a preferred amorphous solid electrolyte material, the lithium ion conductivity at 25 °C room temperature is ≥ 1.2×10 -2 S / cm.
[0016] A preparation method of an amorphous solid electrolyte material of the Li-Y-Cl-S system co-doped with Mg, O, and Br elements, comprising the following steps: Step 1: Mix lithium source, yttrium source, sulfur source, chlorine source, bromine source, oxygen source, and magnesium source according to stoichiometric ratio. Perform high-energy ball milling on the mixture for 1-60 hours in an inert atmosphere to ensure thorough mixing and reaction of the components to form a uniform precursor powder. Further, the lithium source is a mixture of Li₂S and LiX, where X is one or both of Cl and Br elements; preferably, Li₂S and LiCl are used simultaneously to provide sulfur and chlorine. Further, the yttrium source is at least one of YCl₃ and Y₂S₃, the bromine source is LiBr, the oxygen source is Li₂O or a precursor that can decompose to generate Li₂O, and the magnesium source is MgC. At least one of l2, MgBr2, or MgO; further, the ball milling process is carried out in a dry inert gas environment with a protective gas dew point ≤ -40℃, and the ball milling media is a high-hardness inert material; further, the ball milling speed is 200-800 rpm, the ball milling time is 12-60 hours, and the metal balls used in the ball milling process are cemented carbide or zirconia ceramic balls, etc.; to control the distribution of halogen elements, a step-by-step feeding ball milling process can be adopted, for example, first ball milling the lithium source, sulfur source, yttrium source, and magnesium source for a certain time, and then adding lithium halides (LiCl, LiBr) and oxygen sources to continue ball milling to ensure uniform dispersion of halogens and oxygen in the mixture. The ball milling process should be carried out in a dry inert gas environment (protective gas dew point ≤ -40℃), and the introduction of moisture is strictly prohibited to prevent hydrolysis or oxidation of the raw materials, which would affect the doping effect. After thorough ball milling, a gray precursor powder with uniform elemental distribution can be obtained.
[0017] Step two involves rapidly heating the precursor powder to 300-600°C in an inert atmosphere and holding it for 0.5-2 hours, followed by rapid cooling to room temperature to obtain the Mg, O, and Br co-doped Li-Y-Cl-S solid electrolyte powder. Further, the precursor powder from step one is placed in a furnace preheated to 400-500°C and held for 0.5-1 hour, then immediately removed and quenched in an inert atmosphere. This rapid heat treatment process promotes atomic diffusion and structural rearrangement within the material. However, the short holding time followed by rapid cooling avoids grain growth and impurity phase precipitation caused by prolonged sintering, thus forming at least a partially amorphous glassy phase structure in the product. Appropriate heat treatment temperature and time can be adjusted according to the doping content: too low a temperature (<300°C) may lead to incomplete reaction, insufficient crystallinity, and low conductivity; too high a temperature or prolonged holding may precipitate unwanted crystalline phases. Therefore, rapid heating combined with quenching is a key step in obtaining high-performance amorphous products.
[0018] The application of a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br in an all-solid-state lithium battery, wherein the all-solid-state lithium battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive and negative electrodes.
[0019] The prepared amorphous solid electrolyte material can be directly used in the assembly of all-solid-state batteries; it can also undergo subsequent mild pressing or short-time sintering to improve the interfacial contact between particles. If it is necessary to prepare a separate electrolyte membrane, the powder can be placed in a mold and pressed into shape at room temperature or under heating conditions to obtain a dense solid electrolyte.
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0021] Example 1 1. Raw material ratio: According to the general chemical formula Li8YS 4.8 O 0.2 Cl 0.2 Br 0.2 Mg 0.1 Weigh the raw materials. The lithium source is Li2S, LiCl, or LiBr; the yttrium source is YCl3; the oxygen source is Li2O; and the magnesium source is MgCl2.
[0022] 2. High-energy ball milling: The raw materials were mixed evenly in an argon glove box, then loaded into a ball mill jar with a ball-to-material ratio of 20:1. The milling media were zirconia ceramic balls. Under argon protection, the mixture was ball-milled at 500 rpm for 30 hours to obtain a gray precursor powder.
[0023] 3. Rapid heat treatment: The precursor powder is placed in a tube furnace under an argon atmosphere and rapidly heated to 450°C. After holding at this temperature for 1 hour, it is quickly removed and cooled to room temperature to obtain electrolyte powder.
[0024] 4. Performance Testing The room temperature ionic conductivity is 1.5 × 10⁻⁶. -2 The S / cm ratio and the activation energy for ion migration are 0.23 eV.
[0025] Exposure to air at 25°C and 50% relative humidity for 24 hours resulted in a mass increase rate of 0.8% and an H2S release concentration of 3 ppm.
[0026] An all-solid-state lithium battery assembled with NMC811 as the positive electrode and copper foil as the negative electrode retained 85% of its capacity after 400 cycles at 25°C and 0.1C rate, and 78% of its capacity after 500 cycles.
[0027] Example 2 1. Raw material ratio: According to the general chemical formula Li8YS4.9 O 0.1 Cl 0.7 Br 0.3 Mg 0.05 Weigh the raw materials. The lithium source is Li2S, LiCl, or LiBr; the yttrium source is YCl3; the oxygen source is Li2O; and the magnesium source is MgCl2.
[0028] 2. High-energy ball milling: The raw materials were mixed evenly in an argon glove box, then loaded into a ball mill jar with a ball-to-material ratio of 20:1. The milling media were cemented carbide balls. Under argon protection, the mixture was ball-milled at 400 rpm for 40 hours to obtain a gray precursor powder.
[0029] 3. Rapid heat treatment: The precursor powder is placed in a tube furnace under an argon atmosphere and rapidly heated to 400°C. It is held at this temperature for 1.5 hours and then quickly removed and cooled to room temperature to obtain electrolyte powder.
[0030] 4. Performance Testing The room temperature ionic conductivity is 1.3 × 10⁻⁶. -2 S / cm, ion migration activation energy is 0.24 eV.
[0031] Exposure to air at 25°C and 50% relative humidity for 24 hours resulted in a mass increase rate of 0.9% and an H2S release concentration of 4 ppm.
[0032] An all-solid-state lithium battery assembled with NMC811 as the positive electrode and copper foil as the negative electrode retained 82% of its capacity after 400 cycles at 25°C and 0.1C rate, and 76% of its capacity after 500 cycles.
[0033] Example 3 1. Raw material ratio: According to the general chemical formula Li8YS 4.85 O 0.15 Cl 0.75 Br 0.25 Mg 0.08 Weigh the raw materials. The lithium source is Li2S, LiCl, or LiBr; the yttrium source is YCl3; the oxygen source is Li2O; and the magnesium source is MgCl2.
[0034] 2. High-energy ball milling: A stepwise feeding process is adopted. First, the lithium source, sulfur source, yttrium source and magnesium source are ball milled at 600 rpm for 20 h. Then, lithium halide and oxygen source are added, and ball milling is continued at 500 rpm for 15 h to obtain gray precursor powder.
[0035] 3. Rapid heat treatment: The precursor powder is placed in a tube furnace under an argon atmosphere and rapidly heated to 500°C, held at that temperature for 0.8 h, and then quickly removed and cooled to room temperature to obtain electrolyte powder.
[0036] 4. Performance Testing The room temperature ionic conductivity is 1.4 × 10⁻⁶. -2 The S / cm ratio and the activation energy for ion migration are 0.22 eV.
[0037] After 24 hours of exposure to air at 25°C and 50% relative humidity, the mass increase rate was 0.84%, and the H2S release concentration was 2.5 ppm.
[0038] An all-solid-state lithium battery assembled with NMC811 as the positive electrode and copper foil as the negative electrode retained 84% of its capacity after 400 cycles at 25°C and 0.1C rate, and 77% of its capacity after 500 cycles.
[0039] Comparative Example 1. Raw material ratio: Undoped Li–Y–Cl–S electrolyte.
[0040] 2. Performance Testing The room temperature ionic conductivity is 1.0 × 10⁻⁶. -3 The S / cm ratio and the activation energy for ion migration are 0.32 eV.
[0041] Exposure to air at 25°C and 50% relative humidity for 24 hours resulted in a 5% increase in mass and an H2S release concentration of 30 ppm.
[0042] An all-solid-state lithium battery was assembled using NMC811 as the positive electrode and copper foil as the negative electrode. After 400 cycles at 25°C and 0.1C rate, the capacity retention rate was 45%.
[0043] Example Conclusion Single-doping performance and mechanism analysis: To verify the role of each doping element in improving performance, the inventors of this invention referred to the performance impact data of single-element doping on similar halide-sulfide electrolyte systems and summarized the changes in material properties when Mg, O, and Br are doped individually as follows: Mg doping: Introducing trace amounts of Mg into the matrix 2+ (e.g., 0.05-0.1 at%) can produce equal concentrations of Li in the crystal lattice. + Vacancies are created, thereby increasing the number of lithium-ion carriers and providing more migration channels. Experimental results show that the ionic conductivity of the undoped sample at 25℃ is approximately 1.2 × 10⁻⁶. -3 The S / cm ratio increased to approximately 1.5 × 10⁻⁶ after Mg doping. -3The S / cm ratio was increased by approximately 20-30%; simultaneously, the activation energy Ea for ion migration decreased from approximately 0.26 eV to 0.22-0.24 eV. The small amount of Mg doping had minimal impact on the material's crystal phase; the position of the main XRD peak showed only a slight shift of less than ±0.1°, and the material maintained its original phase structure. In all-solid-state batteries, the Mg-doped electrolyte slightly slowed the rate of increase in interfacial impedance: in batteries assembled with NMC811 cathode / Li metal anode, the Mg-doped electrolyte increased the capacity retention after 300 cycles from approximately 80% of the control to 85-88%, and after 500 cycles from approximately 72% to approximately 78-80%. Furthermore, Mg doping did not reduce the material's resistance to hydrolysis: after being placed in dry air at a dew point of -40°C for 72 hours, the Mg-doped sample showed a weight gain of approximately 0.5% and an H2S release concentration of <0.5 ppm, both slightly lower than the undoped sample (approximately 0.8% weight gain and 0.8 ppm gas).
[0044] O doping: with O 2- After equivalent substitution of some sulfur, the overall charge of the material remains unchanged, but the anionic polarity increases and the chemical bond energy rises, thereby enhancing the structural rigidity and chemical stability of the material. The oxygen-doping experiments compiled in this invention show that after doping approximately 10 mol% oxygen (with adjustments for the halogen ratio) into the Li-Y-Cl-S system, the room-temperature ionic conductivity can still be maintained at 1.6-1.7 × 10⁻⁶. -3 The S / cm concentration was comparable to that of the undoped optimized matrix sample; while Ea decreased from approximately 0.31 eV to approximately 0.26 eV. More notably, the air resistance was significantly improved: the undoped Li-Y-Cl-S matrix sample gained approximately 2% weight after 0.5 hours of exposure to air with a relative humidity of ≈50%, and approximately 5% weight after 24 hours, with H2S concentration reaching tens of ppm, resulting in discoloration and agglomeration; while the oxygen-doped sample, under the same conditions, gained only 0.5% weight after 0.5 hours, and <1% total weight after 24 hours, with H2S only detected at an initial moment of <5 ppm, subsequently rapidly decreasing to background levels, and no significant change in the material's crystal phase. This indicates that oxygen doping effectively passivates active sites such as Li2S, significantly reducing the driving force for the reaction with moisture. On the other hand, oxygen doping also improves the interfacial compatibility between the electrolyte and the lithium metal anode: during battery cycling, a stable lithium salt layer rich in Li3OCl can be generated in situ at the interface, which has ionic conductivity and electronic insulation, can block electron transfer and stabilize the interface, and suppress further side reactions and lithium dendrite growth. Actual measurements of NMC811 cathode / copper foil (without a pre-placed lithium anode, i.e., "anode-free" configuration) batteries show that the oxygen-doped electrolyte battery retains approximately 82% of its capacity after 400 charge-discharge cycles at 0.1C, far exceeding the <50% retention rate of the undoped control group, proving that oxygen doping greatly improves the long-cycle stability of the battery.
[0045] Br doping: with Br- Partially replaces Cl - This increases the lattice parameters and anion spacing, widening the lithium-ion diffusion path and increasing the disorder of anion sites. Data shows that introducing 20-30 mol% Br into Li-Y-Cl-S materials increases the ionic conductivity at 25℃ from approximately 1.2 × 10⁻⁶ mol% to the undoped form. -3 S / cm jumps to ~1.7×10 -3 The S / cm conductivity increased by approximately 40%, while Ea decreased from 0.31 eV to approximately 0.28 eV. This demonstrates the significant effect of Br on improving conductivity. However, Br doping alone has limited improvement on moisture stability: Br-doped samples without oxygen, after being placed in air with approximately 50% RH for 24 hours, showed a weight gain of about 3%, and the H2S peak was still ~20 ppm, although lower than the undoped sample, it was far inferior to the oxygen-doped sample. Regarding interfacial performance, the initial performance of batteries assembled with Br-doped electrolytes was similar to the undoped control, but the capacity began to decline significantly after about 200 cycles, and the capacity retention was only about 60% after 400 cycles, with a significant increase in interfacial impedance. This indicates that Br doping mainly contributes to improving ionic conductivity, while its inhibitory effect on interfacial side reactions is relatively limited, requiring combination with other dopants to fully realize its potential.
[0046] The experimental results of single-element doping show that Mg doping significantly improves the lithium-ion migration rate through vacancy effects, O doping significantly enhances the material's resistance to moisture and interfacial stability, and Br doping improves conductivity and has a certain promoting effect on the interface through lattice expansion. This establishes the design concept of co-doping with these three elements, aiming for a synergistic effect: Mg creates more charge carriers and migration channels, Br provides a more relaxed and disordered diffusion space, and O ensures the chemical stability of the material and passivates the interface, thereby achieving superior overall performance compared to any single modification.
[0047] Ternary synergistic enhancement mechanism: After ternary co-doping with Mg, O, and Br, the following synergistic mechanism is generated within the material of this invention: Lowering the vacancy formation energy and increasing the carrier concentration: The incorporation of O element increases lattice rigidity and disorder, which helps stabilize Li generated by Mg doping. + Vacancy, thus reducing the vacancy formation energy. In other words, in a ternary doped system, it is easier to maintain a high concentration of Li. + Vacancies are created without causing lattice collapse, further increasing lithium-ion carrier concentration and mobility.
[0048] Stabilizing amorphous structures and alleviating grain boundary barriers: Multi-element doping increases the complexity of material composition, strongly hindering long-range ordered crystal growth and making materials more prone to forming amorphous or glassy structures. The absence of grain boundaries in amorphous structures effectively avoids ion migration barriers caused by space charge layers at grain boundaries. Therefore, ternary doping is beneficial for stabilizing the amorphous phase of materials and may induce local structural micro-distortions, resulting in a more "flat" migration barrier distribution. This also explains why the material of this invention can achieve millisiemens-level ionic conductivity while maintaining high stability.
[0049] Optimizing interface configuration and improving interface stability: O element endows the material with the ability to form a stable passivation layer with Li2O / Li3OCl composition in situ on the lithium anode surface. This in-situ formed oxygen-rich halide interface phase has both good ionic conductivity and electronic insulation, which can effectively suppress further interfacial side reactions and lithium dendrite growth. The presence of Br element makes the electrolyte / electrode interface contact tighter: on the one hand, Br - Doping improves the ionic conductivity and flexibility of the electrolyte material surface, which is beneficial for filling the microscopic gaps between the electrolyte and the electrode; on the other hand, Cl... - With Br - The coexistence of these factors increases the diversity of interfacial reaction products, such as the potential formation of small amounts of mixed halides like LiBr and LiCl, which, together with Li₂O / Li₃OCl, form a stable and dense composite SEI passivation layer. Mg doping improves the ionic conductivity of the electrolyte bulk and reduces the ion concentration gradient at the interface, thereby decreasing the interfacial polarization voltage. The synergistic effect of these three factors results in a more optimized battery interface structure—it possesses both a dense, inert inorganic passivation layer to block side reactions and maintains good ion channels, significantly reducing interfacial impedance and improving battery cycle life.
[0050] The above mechanism analysis shows that the ternary co-doping of the present invention produces a synergistic effect at multiple levels, including lattice defects, phase structure, and interface chemistry. This synergistic effect makes the overall performance of the material far exceed that of the traditional Li-Y-Cl-S system, which is the fundamental reason for the high performance of the material of the present invention.
[0051] Comparison with unmodified materials (Comparative Example 1): To highlight the performance improvement of the ternary doped system, the following comparisons are made between the material of this invention and conventional undoped Li-Y-Cl-S materials in terms of key performance indicators: Room temperature ionic conductivity (25℃): approximately 10 for undoped Li-Y-Cl-S material. -3 S / cm (typical value ~1×10) -3 (S / cm), the ternary doped material of this invention is ≥1.2×10 -2 S / cm, an improvement of approximately one order of magnitude; Ion migration activation energy Ea: approximately 0.30-0.31 eV for undoped materials, reduced to ~0.25 eV for the material of this invention, a reduction of approximately 15-20%; Interface impedance (measured with Li symmetric cells): The initial interface impedance of the undoped electrolyte is several hundred Ω and increases rapidly. The battery short-circuits due to interface failure in less than 300 hours of operation. The initial interface impedance of the electrolyte of this invention is <150Ω, and it is stable in long-term cycling. There are no signs of short-circuit failure after >800 hours. Full cell cycle performance (NMC811 positive electrode / / lithium metal negative electrode assembly, all-solid-state battery): The battery using the undoped electrolyte rapidly decays in capacity after 100 cycles at 0.1C, and the remaining discharge capacity is less than 50% after 400 cycles; while the battery using the electrolyte of this invention retains >80% of its capacity after 400 cycles at 0.1C, and no internal short circuit or rapid decay occurs. Stability in air (25℃, 50% relative humidity): Undoped samples showed a weight gain of >2% after 0.5 hours of exposure, a weight gain of ≥5% after 24 hours, and H2S release of tens of ppm; while the doped samples of this invention showed a weight gain of ~0.5% after 0.5 hours, a total weight gain of <1% after 24 hours, and an H2S concentration of <5 ppm, which was only a trace amount. Preparation environment requirements: Undoped Li-Y-Cl-S materials must be operated under extremely dry conditions (dew point < -40℃) and there is a risk of releasing toxic H2S gas; the doped materials of this invention have relatively relaxed environmental requirements and can be exposed to dry air with ≤50%RH for a short time without significant performance degradation and with virtually no release of toxic gas.
[0052] Optional embodiments and applicable scope: Based on the above preferred embodiments, the present invention also covers several variant embodiments and parameter adjustments to expand the scope of protection and improve the adaptability of the formulation: Doping elements and their proportions: Mg can be replaced with other doping elements that have a similar 2+ valence effect, such as Ca. 2+ 、Sr 2+ Alkaline earth metals, through Li + Vacancy mechanisms can also improve conductivity. However, due to Mg... 2+ Due to its small ionic radius and minimal lattice disturbance, Mg is the preferred doping element in this invention. Halogen Br - It can also be partially replaced with I - or F - Other halogen elements are co-doped to form a disordered structure in which multiple halogens coexist. Among them, F - The introduction of [a specific component] is expected to form a passivation layer of LiF composition at the interface, further reducing the interface impedance; I - The larger ionic radius of I could further increase ionic conductivity, but I -The compound exhibits poor chemical stability, requiring careful control of the doping amount. Regarding anion doping, equivalent group VI selenium (Se) can, in principle, also be used. 2- While some sulfur or oxygen can be replaced by selenium (Se), considering the potential adverse effects of toxicity and electronegativity differences, this invention preferably uses oxygen (O) as the anion doping source. All substitution or co-doping schemes of the aforementioned doping elements fall within the scope of protection of this invention.
[0053] Raw material and process adjustments: In terms of preparation methods, the ball milling step can be performed using different types and specifications of high-energy ball milling equipment (such as planetary ball mills, stirred mills, etc.) depending on the production scale. High-hardness inert materials such as cemented carbide or zirconia ceramics can be used for the ball milling media, but wear should be avoided to prevent the introduction of impurities such as Fe. If necessary, a polymer liner such as PE can be used to line the inner wall of the ball mill jar to reduce metal contamination. In the heat treatment step, rapid heating can be achieved using a tube furnace or rapid heating via pulsed current in spark plasma sintering (SPS), but rapid cooling after heating is essential to form an amorphous phase. The heat treatment atmosphere is generally an inert gas, but a small amount of dry air or oxygen can be briefly introduced at the end of annealing to remove impurities in situ (e.g., eliminating residual Li2O2), but excessive oxidation of the matrix material must be prevented.
[0054] Composite Modification Applications: The electrolyte material of this invention can also be used in combination with other solid-state electrolytes to leverage their respective advantages. For example, the prepared Mg / O / Br co-doped Li-Y-Cl-S electrolyte can be mixed with a high-ionic-conductivity sulfide electrolyte (such as Li6PS5Cl, i.e., LPSC) in a certain proportion to prepare a composite solid-state electrolyte. The sulfide phase provides higher overall ionic conductivity and good interfacial wettability, while the halide phase provides interfacial stability and mechanical support. According to literature reports, combining Li2ZrCl6 with 30wt% Li6PS5Cl can significantly improve the cycle performance of all-solid-state batteries; similarly, combining the electrolyte of this invention with LPSC can further reduce interfacial impedance and increase critical current density. Furthermore, the material of this invention can also be coated on the electrode surface as an interfacial modification layer, or blended with polymer electrolytes to prepare flexible electrolyte membranes, etc., to meet different application requirements.
[0055] Application Range: The material of this invention maintains stable ion conductivity characteristics (non-limiting value) within a temperature range of -20℃ to 150℃, adapting to battery operating environments from low to medium-high temperatures. In high-voltage cathode (such as nickel-rich layered oxides, lithium-rich manganese-based materials) and lithium metal anode systems, this material exhibits good electrochemical stability and compatibility; however, this invention is not limited to these, and is also applicable to other types of battery systems such as silicon-carbon anodes or lithium alloy anodes. For different types of all-solid-state batteries, the doping ratio and processing conditions of this material can be fine-tuned to achieve optimal performance: for example, for high-voltage lithium-rich cathode systems, the total halogen content in the material can be appropriately increased (e.g., increasing the Cl / Br ratio) to enhance oxidation resistance; for high-rate discharge requirements, the Mg doping amount can be slightly increased to approximately 0.5 at% to further reduce the internal impedance of the electrolyte. Through the above various modifications, this invention provides a wide range of parameter adjustment space, giving the material system good flexibility and compatibility. Any equivalent substitutions or improvements made in the above aspects, as long as they follow the core idea of this invention (i.e., the synergistic mechanism of simultaneously utilizing Mg vacancy doping, O anion doping, and Br halogen doping), should be considered to fall within the protection scope of this invention.
[0056] Feasibility and Application Scenarios: The preparation method of the Mg / O / Br ternary co-doped Li-Y-Cl-S solid electrolyte described in this invention is mature and feasible. The required raw materials are all common industrial chemical raw materials (such as Li2S, YCl3, LiCl, LiBr, MgCl2, Li2O, etc.), which are inexpensive and easy to procure in bulk. The process route mainly uses mechanical ball milling and low-temperature rapid heat treatment, avoiding high-temperature long-term sintering. This not only results in lower energy consumption but also helps to maintain the amorphous structure of the material. The process steps are simple and controllable, making it suitable for large-scale preparation of high-performance solid electrolyte powders. Samples prepared under laboratory conditions have verified the performance advantages of the material of this invention. The results show good repeatability and stability, indicating that the scheme of this invention is fully feasible.
[0057] In the application of all-solid-state lithium batteries, the electrolyte material of this invention exhibits great potential and wide applicability. On the one hand, its room-temperature ionic conductivity reaches the millisiemens per centimeter level (approximately 10⁻⁶). -2(S / cm level), meeting the requirements of high-speed charge and discharge of all-solid-state batteries at room temperature. This means that batteries using the electrolyte of this invention can operate at higher rates without excessively sacrificing capacity, thereby improving the battery's power density. On the other hand, the material's excellent interface stability and moisture resistance reduce the stringent environmental requirements for battery manufacturing and operation: due to its insensitivity to moisture, the electrolyte powder can be briefly exposed to dry air without significant degradation, reducing the dependence on anhydrous and oxygen-free environments during battery packaging; when in contact with the lithium metal anode, it can generate a stable Li3OCl / LiCl lithium-rich passivation layer in situ, effectively suppressing side reactions and lithium dendrite growth at the anode, enabling the battery to operate stably for long periods without additional artificial interface coatings, even when using a high-specific-capacity lithium metal anode. These characteristics are crucial for the large-scale manufacturing and safe operation of all-solid-state batteries.
[0058] Specific applications include, but are not limited to, high-energy-density all-solid-state batteries using NMC811 or other nickel-rich cathode materials in conjunction with lithium metal anodes, which can be used in fields such as electric vehicle power batteries and aerospace power supplies. In such batteries, the electrolyte of this invention can fully utilize its high oxidation stability (robustly withstanding cathode potentials >4V) and interface self-passivation capability (generating a stable Li3OCl / LiCl layer in situ with the lithium anode), effectively preventing the decomposition of the cathode under high voltage and the dendrite growth of the anode, achieving a revolutionary improvement in battery cycle life and safety. Simultaneously, due to the material's excellent mechanical properties and high interparticle interface matching, the electrolyte sheet can be cold-pressed to fit tightly with the electrode, reducing interfacial contact resistance and enabling the battery to output stable voltage and capacity at medium to high rates. Furthermore, the material system of this invention also shows promise in flexible wearable batteries, micro all-solid-state batteries, and large-scale energy storage solid-state batteries. Its good air stability reduces the requirements for sealing conditions during battery assembly and transportation, improving product consistency and reliability; its high ionic conductivity and low interfacial impedance help extend the operating temperature range of all-solid-state batteries and improve low-temperature performance. It is foreseeable that the all-solid-state lithium battery using the solid electrolyte of this invention will simultaneously possess the advantages of high energy density, high safety, and long cycle life, and is expected to accelerate the commercialization process of all-solid-state batteries and provide new technical solutions for the new energy industry.
[0059] In summary, the Mg, O, and Br co-doped Li-Y-Cl-S solid electrolyte material provided by this invention, through meticulous composition design and experimental verification, can effectively address key pain points in existing solid-state battery technologies. Its preparation method is simple and feasible, and the product exhibits excellent performance, demonstrating practical application value and broad prospects in next-generation high-energy-density all-solid-state lithium batteries.
[0060] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br, characterized in that, The chemical general formula is: Li a Y b S d-z O z Cl c-y Br y Mg w , where 0.1 ≤ z ≤ 0.3, 0 < y ≤ 0.4, 0 < w ≤ 0.3, the value range of a is 5 - 10, the value range of b is 0.5 - 2, the value range of c is 0.4 - 1, and the value range of d is 4 - 5.
2. The Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br as described in claim 1, characterized in that, The general chemical formula is: Li8YS 5-z O z Cl 1-y Br y Mg w Where 0.1≤z≤0.3, 0 <y≤0.4,0.05<w≤0.3。 3. The Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br as described in claim 1, characterized in that, The amorphous solid electrolyte material contains 0.1 at%.
4. The Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br as described in claim 1, characterized in that, The amorphous solid electrolyte material has a lithium-ion conductivity ≥1.2×10⁻⁶ at room temperature (25°C). -2 S / cm.
5. A method for preparing a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br as described in any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Mix lithium source, yttrium source, sulfur source, chlorine source, bromine source, oxygen source and magnesium source according to stoichiometric ratio, and perform high-energy ball milling on the mixture in an inert atmosphere for 1-60 hours to ensure that the components are fully mixed and reacted to form a uniform precursor powder. Step 2: The precursor powder is rapidly heated to 300-600°C in an inert atmosphere and held for 0.5-2 hours, and then rapidly cooled to room temperature to obtain the Mg, O, Br co-doped Li-Y-Cl-S solid electrolyte powder.
6. The method for preparing a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br according to claim 5, characterized in that, In step one, the lithium source is a mixture of Li2S and LiX, wherein X is one or both of Cl and Br elements; the yttrium source is at least one of YCl3 and Y2S3; the bromine source is LiBr; the oxygen source is Li2O or a precursor that can decompose to generate Li2O; and the magnesium source is at least one of MgCl2, MgBr2, or MgO.
7. The method for preparing a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br according to claim 5, characterized in that, In step one, the ball milling process is carried out in a dry, inert gas environment with a protective gas dew point ≤ -40℃, and the ball milling media is a high-hardness inert material.
8. The method for preparing a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br according to claim 5, characterized in that, In step one, the ball milling speed is 200-800 rpm, and the ball milling time is 12-60 hours.
9. The method for preparing a Li-Y-Cl-S amorphous solid electrolyte material co-doped with Mg, O, and Br according to claim 5, characterized in that, Step two specifically involves placing the precursor powder described in step one into a furnace preheated to 400-500°C and maintaining it for 0.5-1 hour, then immediately removing it and quenching it in an inert atmosphere.
10. The application of a Li-Y-Cl-S amorphous solid-state electrolyte material co-doped with Mg, O, and Br as described in any one of claims 1-4 in an all-solid-state lithium battery, characterized in that, The all-solid-state lithium battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive and negative electrodes; the solid electrolyte layer adopts the Mg, O, Br co-doped Li-Y-Cl-S solid electrolyte material as described in any one of claims 1-4.
Citation Information
Patent Citations
Solid electrolyte material and preparation method and application thereof
CN115676883A
Solid electrolyte material and preparation method and application thereof
CN115966756A